2017
DOI: 10.3390/molecules22081359
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Accumulation of Sulfur Compounds and Saponins in Different Parts of Garlic Cloves from Purple and White Ecotypes

Abstract: This study set out to determine the distribution of sulfur compounds and saponin metabolites in different parts of garlic cloves. Three fractions from purple and white garlic ecotypes were obtained: the tunic (SS), internal (IS) and external (ES) parts of the clove. Liquid Chromatography coupled to High Resolution Mass spectrometry (LC-HRMS), together with bioinformatics including Principal Component Analysis (PCA), Hierarchical Clustering (HCL) and correlation network analyses were carried out. Results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 37 publications
0
43
0
2
Order By: Relevance
“…Prior to analysis, 10 mg of freeze-dried fruit powder from each sample were weighed and extracted (i) with 0.75 mL cold 75% (v/v) methanol with for 0.5 mg/L formononetin as internal standard (IS) for P metabolites, as previously described [29]; and with (ii) 0.25 mL cold 100% (v/v), 1 mL of chloroform spiked with 25 mg/L α-tocopherol acetate as internal standard and 0.25 mL 50 mM Tris buffer (pH 7.5, containing 1 M NaCl) as described in [30]. Liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS) conditions were as previously reported for, respectively, polar [31] and non-polar [32] metabolomes.…”
Section: Non-volatile Detection and Quantificationmentioning
confidence: 99%
“…Prior to analysis, 10 mg of freeze-dried fruit powder from each sample were weighed and extracted (i) with 0.75 mL cold 75% (v/v) methanol with for 0.5 mg/L formononetin as internal standard (IS) for P metabolites, as previously described [29]; and with (ii) 0.25 mL cold 100% (v/v), 1 mL of chloroform spiked with 25 mg/L α-tocopherol acetate as internal standard and 0.25 mL 50 mM Tris buffer (pH 7.5, containing 1 M NaCl) as described in [30]. Liquid chromatography coupled to high-resolution mass spectrometry (LC-HRMS) conditions were as previously reported for, respectively, polar [31] and non-polar [32] metabolomes.…”
Section: Non-volatile Detection and Quantificationmentioning
confidence: 99%
“…In 1550 B.C., antibiotics and pharmacy products were not available so garlic was used for medicinal purposes in different epidemics, such as typhus, dysentery, cholera, and influenza [ 2 ]. The therapeutic effects of garlic are mainly due to the impressive activity of its bioactive compounds, such as organic sulfides [ 3 ], saponins [ 4 ], phenolic compounds [ 5 ], and polysaccharides [ 6 ]. For example, several in vitro and in vivo studies have showed that garlic compounds are able to modulate various signaling pathways, including nuclear factor-κB and wingless-related integration site [ 7 ], matrix metalloproteinases, nuclear factor erythroid 2 like 2, protein kinase B (pAkt), mitogen-activated protein kinase, c-Jun N-terminal kinases, caspases, p38, transforming growth factor beta 1 (TGF-β1), TGF-β type II receptor, psmad2/3, smad4 and smad7 [ 8 , 9 ], cytokines, intercellular adhesion molecule [ 10 ], notch pathway [ 11 ], 5’ AMP-activated protein kinase pathway [ 12 ], vascular endothelial growth factor [ 13 ], cyclooxygenase 2, inducible nitric oxide synthase, Akt/mTOR [ 14 ], and Keap1 [ 15 ], leading to improved anti-inflammatory and antioxidant properties, as well as chemopreventive, antiproliferative, anti-angiogenic, antidiabetic, and cardioprotective effects.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, transcriptomes from Gardenia jasmonoides , Bixa orellana , Buddleja davidii , and Crocus sieberi have been published [ 45 , 46 , 47 ]. We manually looked for different ALDHs genes from these species and selected three from G. jasminoides (KY631926, KY631927 and KY631928) and one B. davidii (accession number MH182707) and C. sieberi (c74954_g1_i1 transcriptome accession PRJNA413953) based on their expression pattern matching with the accumulation of crocins, and one ALDH from Bixa orellana (accession number CAD70189.1) species that accumulates the C-24 apocarotenoid bixin, which has been selected using the same criteria.…”
Section: Resultsmentioning
confidence: 99%